Cryptocurrencies: An Analysis of How Allocation Affects the Risk-Return Characteristics of a Portfolio - Auvinen, Julia (My University, 2023)
In 2008, the first blockchain-based digital currency named Bitcoin was released. More than ten years later, dozens of cryptocurrencies and countless additional usage for blockchain technology are broadly available in financial markets. Alongside with the previous years’ market growth, the appreciation of major cryptocurrencies has also been exceptionally robust. The significant upswing in returns and low correlation with traditional asset classes has increasingly piqued investors’ interest in this new investment instrument and its potential applications. The aim in this thesis is to investigate the usability and efficiency of cryptocurrencies as an investment instrument from an investor’s point of view. More specifically, how the allocation of cryptocurrencies impacts portfolio optimization in a traditional asset class-based portfolio. Since cryptocurrencies are detached from traditional financial markets, no specific asset has disproportionate impact on the value of cryptocurrencies. The low correlation between cryptocurrencies and traditional asset classes indicates potential diversification benefits in the context of an investment portfolio. In this thesis, potential diversification benefit from the cryptocurrency allocation is observed with the shift of an efficient frontier. In the thesis, three cryptocurrencies (Bitcoin, Ethereum, and XRP) are allocated to an investment portfolio constructed from traditional asset classes (stocks, bonds, FX, and commodities) utilizing Markowitz's (1952) portfolio theory. The statistical significance of the diversification benefit in this thesis has been assessed using Huberman and Kandel's (1987) spanning test. The empirical research resulted in all three cryptocurrencies and cryptocurrency index shifting efficient frontier upwards measure with increase of Sharpe ratio. The spanning test (Huberman & Kandel, 1987) confirms the statistical significance of the improvement yielded from the allocation of cryptocurrency index, Bitcoin, and Ethereum. However, the results of XPR’s spanning test were not statistically significant. These findings support the literature review’s view that cryptocurrencies may be an appealing diversifier in the context of a traditional asset portfolio.

Vuonna 2008 esiteltiin ensimmäistä kertaa lohkoketjuteknologiaan pohjautuva digitaalinen valuutta Bitcoin. Noin vuosikymmen myöhemmin, tuhansia kryptovaluuttoja ja muita lohkoketjuteknologiaan pohjautuvia sijoituskohteita on saatavilla rahoitusmarkkinoilla. Edellisten vuosien voimakkaan maailmanlaajuisen markkinakasvun ohella myös suurimpien kryptovaluuttojen arvonousu on ollut poikkeuksellisen voimakasta. Tuottojen voimakas nousu ja vähäinen korrelaatio perinteisten omaisuuslajiluokkien kanssa on herättänyt kasvavassa määrin sijoittajien mielenkiintoa tätä uutta sijoituskohdetta sekä sen potentiaalisia käyttömahdollisuuksia kohtaan. Tämän tutkielman tarkoituksena on tarkastella kryptovaluuttojen käyttömahdollisuuksia sijoittajan näkökulmasta. Tarkennettuna, miten kryptovaluuttojen allokaatio vaikuttaa perinteisistä omaisuuslajiluokista rakennetun sijoitusportfolion kokonaistuottoon. Koska sijoitus instrumentteina kryptovaluutat ovat irrallisia perinteisistä rahoitusmarkkinoista, yhdelläkään perinteisellä omaisuuslajilla ei ole havaittua suoraa vaikutusta kryptovaluuttojen arvonmuodostukseen. Vähäinen korrelaatio kryptovaluuttojen ja perinteisien omaisuuslajiluokkien välillä indikoi mahdolliseen hajautushyötyyn sijoitusportfoliokontekstissa. Mahdollista hajautushyötyä tarkastellaan tutkielmassa tehokkaan rintaman mahdollisella siirtymällä. Tutkielmassa kolme kryptovaluuttaa (Bitcoin, Ethereum ja XPR) allokoidaan perinteisitä omaisuuslajiluokista (osakkeet, velkakirjat, valuutat ja hyödykkeet) rakennettuun sijoitusportfolioon Markowitzin (1952) portfolioteoriaa hyödyntäen. Hajautushyödyn tilastollista merkitsevyyttä tässä tutkielmassa on arvioitu Hubermanin & Kandelin (1987) spanning -testillä. Empiirinen tutkimus osoitti, että kaikki kolme kryptovaluuttaa ja kryptovaluuttaindeksi siirsivät tehokasta rintamaa ylöspäin ja paransivat näin portfolion tuotto/riski -suhdetta Sharpen luvulla mitattuna. Kryptovaluutta indexin, Bitcoinin ja Ethereumin allokaation luoma hajautushyöty vahvistettiin tilastollisesti merkitseväksi Hubermanin & Kandelin (1987) spanning -testillä. Empiirisen analyysin tulokset tukevat kirjallisuuskatsauksen näkemystä siitä, että kryptovaluutat saattavat olla houkuttelevia hajauttajia perinteisen omaisuusluokan salkun rakennuksessa.
Keywords: Cryptocurrency, multi asset portfolio, diversification, portfolio optimization, spanning test